2015
DOI: 10.1111/ecc.12292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pelvic floor muscle exercise on faecal incontinence in rectal cancer patients after stoma closure

Abstract: The purpose of this study was to examine the effects of pelvic floor muscle exercise (PFME) on the faecal incontinence (FI) of rectal cancer patients following stoma closure. Participants were randomly distributed into an exercise group (n = 27) and non-exercise group (n = 26). An experimental design and longitudinal approach were implemented for data collection. Baseline data were collected at 1 day before discharge, and then PFME was taught before the patients were discharged from the hospital. We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“… 24 35–39 There is only one randomised controlled trial (RCT) on a large sample size. 40 Lin et al showed a short-term effect of PFMT on faecal incontinence after LAR. Unfortunately, this study exclusively focused on faecal incontinence, while LARS includes several other bowel symptoms than incontinence, such as incontinence for flatus, frequency of bowel movements, urgency and clustering.…”
Section: Introductionmentioning
confidence: 99%
“… 24 35–39 There is only one randomised controlled trial (RCT) on a large sample size. 40 Lin et al showed a short-term effect of PFMT on faecal incontinence after LAR. Unfortunately, this study exclusively focused on faecal incontinence, while LARS includes several other bowel symptoms than incontinence, such as incontinence for flatus, frequency of bowel movements, urgency and clustering.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of curing FI, main therapies are anal sphincter repair , reconstruction of anal sphincter , colostomy , and sacral nerve stimulation . However, none of these therapies is suitable for all FI situations.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these therapies is suitable for all FI situations. Meanwhile, the rate of complication after these therapies can reach to 21%~71% [7][8][9][10][11] . As the result of that, AAS is launched to create another therapy for FI.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that individuals with urogenital and colorectal cancers are more likely to experience urinary and/or fecal incontinence as a result of their cancer or of the treatment for their disease. 1,2,3 Dysfunction in any of these areas can have significant impact on quality of life including higher levels of depression and anxiety, diminished enjoyment of sexual activity, as well as a significant economic burden in terms of supplies for symptom management. 4,5,6 Assessment of the presence and severity of urinary and fecal incontinence is important for medical professionals to be able to thoroughly gauge disease impact.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a study of individuals with colorectal cancer who underwent resection surgery, over 40% reported liquid stool incontinence and 10% reported solid stool incontinence. 2 The American Physical Therapy Association's (APTA) Evaluation Database to Guide Effectiveness (EDGE) Task Force was created to generate a list of quality outcome measures that are specific to different patient populations with the goal of increasing the implementation of evidence-based practice across the profession. The Oncology Section's EDGE Task Force has reviewed the literature on breast cancer outcomes including scapular and glenohumeral impairments, pain, lymphedema, and fatigue, and they have more recently expanded the evaluation of outcome measures to other types of cancer including urogenital and colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%